Designing, Implementing and Evaluating the Protocol before, during and after Whipple Surgery and Its Effect on the Knowledge, Attitude and Clinical Skills of Surgical Technology Students - Sedigheh Hannani; Parsa Farmahin farahany; Fardin Amiri (پیاورد سلامت)
Background and Aim: The usual trainings are not enough to acquire the knowledge and skills of operating room students to play the role of scrub and mobile person, especially in complex and specialized surgeries. This research was conducted with the aim of determining the effect of designing, implementing and evaluating the protocol before, during and after Whipple surgery and its effect on the knowledge, attitude and clinical skills of surgical technology students of Iran University of Medical Sciences. Materials and Methods: This research was a semi-experimental study of pre- and post-intervention type, during which 50, fifth and seventh semester undergraduate students of surgical technology were selected and trained using the designed protocol.  The content of the protocol included the latest principles of Whipple surgery technology in the field of surgical anatomy, pathology of the digestive system and pancreas, diagnostic procedures and preparations before Whipple surgery, the procedure of Whipple surgery and the post-surgery phase and the recovery period of Whipple surgery.  Before and after the training, the amount of knowledge, attitude and clinical skills of the students were evaluated and compared using a questionnaire and an observational checklist.  The data were analyzed using paired t-test, non-parametric Wilcoxon test and analysis of covariance test in SPSS software. Results: The results of this study showed that after using the designed educational protocol, the knowledge, attitude and clinical skills of surgical technology students increased. That is, the use of the designed educational protocol was effective on the level of knowledge, attitude and especially the clinical skills of the students. So that a statistically significant difference was observed in the average scores of the knowledge, attitude and clinical skill test of the students before and after training (P<0.05). Conclusion: Based on the results of this study, designing and using educational protocols is an effective method in the process of teaching and evaluating the level of knowledge, attitude and clinical skills of students in complex and specialized surgeries such as Whipple surgery. Therefore, the use of educational protocols designed in the process of teaching students is recommended to all professors and educational officials of surgical technology.